Dynamics of Informal Workers in East Java - Jihan Yumn Syahrina; Arfida Boedirochminarni; FX Gugus Febri Purwanto (Jurnal Ilmu Ekonomi JIE, 2026)
The purpose of this research is to examine the characteristics and analyze the factors influencing individuals to become informal workers in East Java. This study employs a quantitative approach using secondary data from the 2023 National Labor Survey. Analysis is carried out using binary logistic regression. The results show that gender, marital status, education, training, internet access, business field, and regional classification significantly affect individuals' likelihood of becoming informal workers in East Java. It indicates that socio-demographic and economic factors also play a role in determining an individual's status as an informal worker, and that collaboration between the government and informal workers is necessary to secure safe and decent jobs.